Ermittlung der möglichen Oberflächen- und Pflanzenverdunstung, dargelegt am Beispiel von Australien: Das Suchen nach einer Formel - Gentilli, J. (ERDKUNDE, 1953)
This study reviews earlier methods used for the estimate of evapotranspiration, i. e. the methods evolved by Prescott (1931, 1949, 1952), by Blaney and Criddle (1945, 1950), and by Thornthwaite (1945, 1948) and Leeper (1950). The first method gives satisfactory results but requires the knowledge of humidity data which are seldom available. The other methods give results which conflict with the theoretical results to be expected from our knowledge of the dominant air masses, especially with regard to the contrast between the western and the eastern coasts. The paper then reviews an entirely new formula suggested by Halstead (1951) from theoretical foundations, which are fully discussed here. The values of potential evapotranspiration computed from this formula agree both with the values measured by tank evaporation and with those expected from air-mass characteristics. The formula is therefore recommended for further study.